2015
DOI: 10.1007/s12070-015-0872-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatization Pattern in Squamousal Type of Chronic Otitis Media

Abstract: To study the pneumatization pattern of mastoid bone in cases of squamousal type of chronic otits media and analyze pneumatization pattern of opposite normal ear in cases of unilateral chronic otitis media (COM). A total of 94 patients (104 ears) between the age group of 7-84 years attending the E.N.T outpatients, inpatients and casualty of Acharya Vinoba Bhave Rural Hospital, Sawangi (Maghe), Wardha, after applying inclusion and exclusion criteria were found suitable and hence selected for the present study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
8
1
1
Order By: Relevance
“…In our study pneumatisation of affected ear was sclerosed in majority of cases which is in agreement with other studies as pneumatisation gets poorer with growing chronicity of the disease, similar where 78.75 % of mastoid sclerosed in study by Amitava. 16 In our study majority of cases were of mucosal type of COM hence cortical mastoidectomy with tympanoplasty was done and in 7 cases modified radical mastoidectomy was done were 2 cases were revision mastoidectomy. None of the patient had any postoperative complications.…”
Section: Age In Yearsmentioning
confidence: 62%
“…In our study pneumatisation of affected ear was sclerosed in majority of cases which is in agreement with other studies as pneumatisation gets poorer with growing chronicity of the disease, similar where 78.75 % of mastoid sclerosed in study by Amitava. 16 In our study majority of cases were of mucosal type of COM hence cortical mastoidectomy with tympanoplasty was done and in 7 cases modified radical mastoidectomy was done were 2 cases were revision mastoidectomy. None of the patient had any postoperative complications.…”
Section: Age In Yearsmentioning
confidence: 62%
“…7 Another study done by Roy et al reported that pneumatisation was seen in 42.6%, diploic in 31.43% and sclerosis in 25.71% patients. 8 In mucosal CSOM ,79% had type Atympanogram,12% had type B and 8.8% had type C whereas in squamosal CSOM 61.53% had type A, 19.23% had type B and 19.23% had type C in CLE. It was in accordance with Jadia et al where they reported Type A in 71% and Type B in 29 % patients.…”
Section: Discussionmentioning
confidence: 89%
“…Roy et al discovered that 1.92% of mastoids were pneumatized, 19.23% were diploic, and 78.85% were sclerotic. Contralateral normal mastoids were pneumatized in 42.86% of cases, diploic in 31.43%, and sclerotic in 25.71% of instances [ 21 ]. Sadé observed an 82.3% association between a low or non-pneumatized mastoid and squamosal COM, whereas Gomaa et al reported a 60.7% association [ 14 , 22 - 24 ].…”
Section: Reviewmentioning
confidence: 99%